2009
DOI: 10.1080/18811248.2007.9711586
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Uranium(VI) from Nitric Acid Solution Using Pyrrolidone Derivatives

Abstract: The extraction behavior of uranyl species from HNO 3 aqueous solutions using CH 2 Cl 2 containing pyrrolidone derivatives as extractants has been studied to find an alternative to tributyl phosphate as an extractant. In this study, we used N-cyclohexyl-2-pyrrolidone (NCP), N-octyl-2-pyrrolidone (NOP), and N-dodecyl-2-pyrrolidone (NDP) as the extractants. As a result, it was found that NCP, NOP, and NDP (abbreviated as NRP) extract U(VI) as UO 2 (NO 3 ) 2 (NRP) 2 , that a part of NCP in CH 2 Cl 2 phase is moved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The extraction behavior of new bi-functional ligands containing sulfur and amide groups towards the U(VI) ion from nitric acid was studied and reported [19][20][21][22][23][24] . Other reports are related to P based extractants used for U extraction [25][26][27][28][29] and our previous extraction studies on U extraction was developed and reported [30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
“…The extraction behavior of new bi-functional ligands containing sulfur and amide groups towards the U(VI) ion from nitric acid was studied and reported [19][20][21][22][23][24] . Other reports are related to P based extractants used for U extraction [25][26][27][28][29] and our previous extraction studies on U extraction was developed and reported [30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%